PELAKSANAAN PEMBINAAN PENDIDIKANNARAPIDANA ANAK DI LEMBAGA PEMASYARAKATAN ANAK PEKANBARU BERDASARKAN UNDANG-UNDANG NOMOR 12 TAHUN 1995 TENTANG PEMASYARAKATAN - WAHYU DERI ALDIS PUTRA; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Implementation of Development of Education inmates children the Correctional Institution Grade II B Pekanbaru, aiming for as a effort and planned to create an atmosphere of learning and the learning process so that learners are actively developing the potential for him to have the spiritual power of religion, self-control, personality, intelligence, character noble and necessary skills themselves, society, nation and country. The purpose writing of this research, namely: first, the implementation of the Development of Education of children inmates at the Correctional Institution Grade II B Pekanbaru. Second, barriers to Development of Education of children inmates at the Correctional Institution Grade II B Pekanbaru. Third, efforts to overcome obstacles in the process of educational development of children inmates at the Correctional Institution Grade II B Pekanbaru.From the results of research can be concluded, first, the implementation of the Development of Education of children inmates at the Correctional Institution Grade II B Pekanbaru, aiming for as a effort and planned to create an atmosphere of learning and the learning process so that learners are actively developing her potential. Second, barriers to Development of Education of children inmates at the Correctional Institution Grade II B Pekanbaru include: lack of teachers, inadequate infrastructure, lack of cooperation with the relevant agencies, the lack of budget allocation for education. Third, efforts to overcome obstacles in the process of Development of Education inmates children the Correctional Institution Grade II B Pekanbaru include: provide educators with adequate, improvement of means of facilities and infrastructure in prisons, increase the allocation to the education budget, cooperation with relevant agencies maximized.Keywords: Children Education, Foster Children, Children's the Correctional Institution